Keanekaragaman dan Kelimpahan Fitoplankton di Rawa Bento, Kerinci sebagai Bioindikator Kualitas Perairan: Diversity and Abundance of Photoplanktone as a Water Quality Bioindicator of Rawa Bento Swamp, Kerinci - Anhar, Vevi; Asra, Revis; Suprayogi, Dawam (Universitas Jambi, 2023)
Phytoplankton is microscopic aquatic organisms that have plant-like properties that act as primary producers of aquatic ecosystems. Bento Swamp is the highest swamp in Sumatra which is included in the Kerinci Seblat National Park (TNKS) area. Bento Rawa plays a role in supporting the lives of the surrounding community as well as being a tourist area. This study aims to identify the diversity and abundance of phytoplankton, as well as their relationship with water quality in Bento Rawa. This research was conducted in February-April 2022 based on the purposive sampling method. The results showed that there were 48 types of phytoplankton belong to 8 classes. The species with the highest abundance in Bento Swamp is Cocconeis sp., Melosira varians, and Fragilaria capucina. The relationship of water quality in Rawa Bento with the diversity and abundance of phytoplankton shows a positive correlation on the parameters of pH, current speed, nitrate, and phosphate. The water quality in Rawa Bento is included in the uncontamined category based on the abudance and diversity of phytoplankton and the measurements of physical and chemical factors in the waters of Rawa Bento obtained in this study Keywords: Phytoplankton, Diversity, Abundance, Water Indicators, Bento Swamp. Â Abstrak Fitoplankton adalah organisme perairan mikroskopis yang memiliki sifat seperti tumbuhan yang bertindak sebagai produsen utama ekosistem perairan. Rawa Bento merupakan rawa tertinggi di Sumatera yang termasuk dalam kawasan Taman Nasional Kerinci Seblat (TNKS). Rawa Bento berperan dalam menunjang kehidupan masyarakat sekitar sekaligus menjadi kawasan wisata. Penelitian ini bertujuan untuk mengidentifikasi keanekaragaman dan kelimpahan fitoplankton, serta hubungannya dengan kualitas perairan di Bento Rawa. Hasil penelitian menunjukkan bahwa terdapat 48 jenis fitoplankton yang termasuk dalam 8 kelas. Spesies dengan kelimpahan tertinggi di Rawa Bento adalah Cocconeis sp., Melosira varians, dan Fragilaria capucina. Hubungan kualitas air di Rawa Bento dengan keanekaragaman dan kelimpahan fitoplankton menunjukkan korelasi positif pada parameter pH, kecepatan arus, nitrat, dan fosfat. Kualitas air di Rawa Bento termasuk dalam kategori tidak tercemar berdasarkan kelimpahan dan keanekaragaman fitoplankton serta pengukuran faktor fisika dan kimia di perairan Rawa Bento yang diperoleh dalam penelitian ini. Kata Kunci: Fitoplankton, Keanekaragaman, Kelimpahan, Indikator Perairan, Rawa Bento.